Enhancement of Students’ Learning Outcomes through Interactive Multimedia - Hadi, Waluyo; Yuksafa, Royana; Yarmi, Gusti; Safitri, Desy; Lestari, Ika; Suntari, Yustia; Umasih; Marini, Arita; Sudrajat, Ajat; Iskandar, Rossi (International Journal of Interactive Mobile Technologies (iJIM), 2022)
Purpose of this study was to determine the effect of using animated video media on student learning outcomes in Solar System science subjects and to determine the improvement in student learning outcomes in class VI SDN Padurenan Jaya. The research design used is a quantitative technique using a quasi-experimental method in the form of Non-Equivalent Control Group Design. The variables in this study are, the independent variable is the use of animation media, while the dependent variable is student learning outcomes. The subjects of this study were students of class VI A and VI B at SDN Padurenan Jaya, totaling 52 students. The sample was determined by purposive sampling, namely, 28 students as the experimental group (VI A) and 26 students as the control group (VI B). Data collection techniques in this study used multiple choice tests in the form of pretest and posttest. Testing the requirements of the hypothesis using normality test (using chi squared analysis technique) and homogeneity test. The validity of the test items was carried out by expert judgment and testing instruments. The reliability of the instrument was test calculated by the Kuder-Richardson formula (KR-20) obtained r = 0.893 which means the reliability of the instrument is very high. The data analysis technique used was a separate group t-test (independent sample test). The t-test was used to determine differences in the level of student learning outcomes. Based on the results of the study, the average score for the pretest control class was 46.54 and the average posttest was 64.04; while in the experimental class the average value of the pretest was 48.39 and the average value of the posttest was 74.82. The increase in learning outcomes for the control class was 17.50 and the experimental class was 26.43. Analysis using all results posttest and tested by t-test with the acquisition of t count > t table (4.775 > 2.021), indicating that Ho is rejected and Ha is accepted, from these results it can be concluded that student learning outcomes using animated video media are greater than the results. Student learning using conventional methods (lectures or blackboards).